Transposition TTIE (Transfer, Translation, Imitate, Evaluation) in Learning Music Notation through Score Creator and Score Cloud - A. Heryanto; Wadiyo Wadiyo; Agus Cahyono; Suharto Suharto (International Conference on Science, Education, and Technology, 2023)
This study aims to determine the application of the concept of TTIE Transposition (Transfer, Translation, Imitate, Evaluation) in Musical Notation Learning through Score Creator and Score Cloud. This research uses Mixed Method. Data collection through tests, observations, documentation and interviews. Furthermore, the data were analyzed based on performance appraisal and triangulation. Based on studies related to the Application of the TTIE Transposition Concept in Learning Music Notation at SMA Negeri 3 Kayuagung it can be stated that the Transposition Concept in Music Notation learning can be successfully revealed through the TTIE Cycle using the Score Creator and Score Cloud applications. The application of the TTIE Transposition Cycle Concept can be carried out in 7 steps; 1) Preparation (Teacher instructs students to bring cell phones, Download Score Creator and bring notational transcripts. 2) The teacher provides an understanding of notation theory and symbols. 3) The Notation Transfer process uses the score creator application. 4) In this translation process, the teacher can clarify the notation that students transfer. 5) The teacher can teach students to sing by following (imitating) the sound in the Score Creator application. 6) students can independently play "Play" and (imitate) the sound of the translation of the Notation on the Score Creator application independently, so that students sing the song Notation correctly. 7) The seventh step is an evaluation of the results of student imitation detected by the Score Cloud application, which can translate the sound of the singer's imitation back into a Notation Transcript.